Robust output feedback controller with high-gain observer for automatic clutch. (1st October 2019) - Shi, Jialei; Li, Liang; Wang, Xiangyu; Liu, Congzhi
Highlights: A novel robust output feedback control method is proposed in this paper to deal with the nonlinearities, uncertainties and modeling errors. A high-gain observer based on output feedback is designed to estimate the unmeasured states. The close-loop stability of proposed controller is proofed. The effectiveness of proposed method is verified on a hybrid electric powertrain bench. Abstract: Precise and stable position control is critical in automatic clutch system, which is a challenging issue because of its nonlinear characteristics, uncertainties of parameters and disturbances, and lack of all-state sensors. Therefore, a novel robust output feedback control method is proposed in this paper to deal with the nonlinearities, uncertainties and modeling errors. First, an electromechanical dry clutch actuator system is formulated by theoretical analysis combined with experimental data. Then, a robust controller is designed, including the recursive control law calculation and a high-gain observer based on output feedback to estimate the unmeasured states. Next, simulations are carried out to verify the effectiveness of proposed method. Finally, experiments are conducted on a hybrid electric powertrain bench and the results show that the proposed method has a satisfactory performance.